66‐4: Understanding the Electron Injection/Transport Mechanism in OLEDs by Using a Superbase as Electron Injection Layer. Issue 1 (28th June 2022) - Sasaki, Tsubasa; Oono, Taku; Okada, Takuya; Hasegawa, Munehiro; Morii, Katsuyuki; Shimizu, Takahisa; Fukagawa, Hirohiko
Abstract : We have found that the work function of aluminum can be reduced to about 2.0 eV by using a superbase as an electron injection layer. This extremely low work function enabled us to gain a complete understanding of the electron injection/transport mechanism in OLEDs.